Phương pháp biến đổi Laplace, phép gần đúng điểm yên ngựa độ chính xác cao ứng dụng cho việc tính mật độ trạng thái dao động của các phân tử trong động học của phản ứng đơn phân tử. Phần 1 - Quý, Trần Vĩnh (Vietnam Journal of Chemistry, 2014)
In the paper the calculation of density of molecular vibration states has been performed by Laplace transformation approach, i.e reduced to the evaluation of inverse Laplace transform of partition function by the aid of saddle point approximation method: The exponential of intergrand in inverse Laplace integral is presented in Taylor series, in which at the saddle point the first derivative vanishes, then, the density of vibration states the inverse Laplace transform is integrated through the steepest descent which is in imaginary direction having the saddle point as abscissa on the real axis. Finally, this process of treatment give the expression of density of vibration states containing terms of from first up to fifth orders of accuracy, which have been easily calculated on computer.